2020
DOI: 10.9734/ijtdh/2020/v41i1330344
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Parents’ Healthcare-Seeking Behaviour for their Sick Children in Nigeria - An Online Survey

Abstract: Introduction: The current COVID-19 pandemic has greatly affected the wellbeing of children, either directly or through the effects of the response. Measures are in place to curb the spread of the virus in Nigeria, but little is known of the effect these stringent measures have on the healthcare-seeking behaviour of parents for their sick children.  Aim: This survey sought to describe parents’ healthcare-seeking behaviour for their sick children during the COVID-19 lockdown in Nigeria. Study Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
2
7
1
2
Order By: Relevance
“…Although insignificant, it was also found that patients whose parents have poor attitudes and behavior related to COVID-19 infection also has an increased rate of abandonment. Previous research among childhood cancer reported that financial burden is the major cause of treatment abandonment, 12 - 14 however our study shows the correlation between socioeconomic impact with abandonment rate of treatment is insignificant. In addition, the difference in COVID-19 knowledge and social support were not significantly related ( Table 3 ).…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…Although insignificant, it was also found that patients whose parents have poor attitudes and behavior related to COVID-19 infection also has an increased rate of abandonment. Previous research among childhood cancer reported that financial burden is the major cause of treatment abandonment, 12 - 14 however our study shows the correlation between socioeconomic impact with abandonment rate of treatment is insignificant. In addition, the difference in COVID-19 knowledge and social support were not significantly related ( Table 3 ).…”
Section: Resultscontrasting
confidence: 78%
“…6,11 There are many factors that influence a person's health seeking behavior, one study about health seeking behavior of mothers in India found that determination of healthcare-seeking behavior is governed by the combination of many factors, such as mother's ages, education, religion, ethnicity, culture, decision-making power, place of residence, and socio-economic status, as well as the cost, quality, and location of healthcare services. 12,13 In this study, we try to explore these factors that influence health seeking behavior in parents' whose children has cancer and associate it with their treatment abandonment during COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Despite adequate knowledge about COVID-19, some participants reported delay in healthcare seeking for routine illnesses during the pandemic. The delay in healthcare seeking [44][45][46][47], including the use of emergency services [48,49], and an increase in self-medication [50] during the pandemic have been reported earlier. This may have resulted in an increase in mortality from non-COVID-19 illnesses such as cardiovascular diseases and neoplasms [51].…”
Section: Discussionmentioning
confidence: 85%
“…This may have resulted in an increase in mortality from non-COVID-19 illnesses such as cardiovascular diseases and neoplasms [51]. A major reason for this is the fear of contracting COVID-19 at healthcare facilities [45,46]. Taken together, the findings highlight the importance of allaying public fear and perception and encouraging people to avail routine healthcare services, irrespective of the COVID-19 status of the patient.…”
Section: Discussionmentioning
confidence: 95%
“…Briggs et al 11 stated that strengthening the health care system and enhancing the accessibility development of contextual strategies are the prime needs to mitigate the pandemic effect and accelerate the health care facility access and utilization by parents during the COVID-19 pandemic. Parents from India believed telemedicine facility as a ray of hope to meet their child’s surgical care needs.…”
Section: Discussionmentioning
confidence: 99%